Implementasi Program Corporate Social Responsibility di Bidang Pendidikan (Studi pada Pemerintah Daerah Kabupaten Kutai Timur dan PT. Kaltim Prima Coal di Kecamatan Bengalon) - Ghoni, Khoirul Abror Ad-Dluha; Wike, Wike; Novita, Asti Amelia (Jurnal Ilmiah Administrasi Publik, 2020)
Education is a strategic area for a nation's change, but Indonesia is not optimistic enough to rely on this position because in reality the conditions and results of education in Indonesia are inadequate. Data published by the United Development Index shows that Indonesia's Human Development Index (HDI) in 2015 was still 113th out of 188 countries. Education in Bengalon district is based on data on dropout rates, the number of level students and education is second place on poverty level indicator. So the government does a partnership with PT. KPC in Corporate Social Responsibility (CSR) programs is one of them in the field of education. This study aims to analyze the implementation of CSR programs in the field of education in Bengalon District. The research method used is descriptive qualitative method. Based on the research that has been done, it is obtained that the implementation of CSR programs in the field of education in Bengalon District has been successfully carried out by PT. KPC is seen from 3 aspects namely Accountability, Transparency, and Sustainability.